A review of flow boiling heat transfer of nanofluids. (5th December 2015) - Fang, Xiande; Wang, Run; Chen, Weiwei; Zhang, Helei; Ma, Chunxiang
Abstract: The flow boiling heat transfer of nanofluids is an important research area which provides many opportunities to explore new frontiers but also poses great challenges. This paper presents a comprehensive review on the flow boiling heat transfer of nanofluids, with an emphasis on the heat transfer coefficient (HTC), critical heat flux (CHF), pressure drop, nanofluid stability, flow and heat transfer mechanism, and flow pattern and bubble dynamics. Most of the available articles have been related to the first four topics. Studies related to the last two topics are rare, which are reviewed because of their importance. The important achievements, inconsistence, and contradictions of the existing research results are identified, and several topics worthy of attention for future investigations are identified. Highlights: Reviews heat transfer and critical heat flux of nanofluid flow boiling. Reviews pressure drop and several flow and heat transfer related topics. Identifies important results, inconsistence, and contradictions of the topics. Suggests the future research directions.